A inquietante estranheza vivenciada por professores na inclusão de alunos com deficiência visual - Azevedo, Tálita Serafim (2021)
This study was brought from the concerns arising from my experience as a blind student, teacher and researcher. It was produced in the Professional Master in Teaching in Basic Education - Graduate Program in Teaching in Basic Education, at the Center for Teaching and Research Applied to Education, at the Federal University of Goiás. The objective of this work is to analyze the relationship between the teacher and the visually impaired student, in a more specific way, to analyze the experience of professionals of Education in the state of Goiás and their reactions in relation to this situation. This is a research with a qualitative and descriptive method, through Life Story approach, using a semi-structured questionnaire and data and content analysis. In addition to the account of the researcher's history, there were 06 teachers (also participants) who were appointed by students with visual impairments. Guided by the semi-structured questionnaire, teachers addressed subjects such as: points that were important in the trajectory as a teacher, choice by the profession, information about initial and continuing education, significant pedagogical actions, perceptions about the visually impaired student in their class, concepts and prejudices in relation to students with disabilities and adopted pedagogical actions. The preliminary results indicate that the majority of the teachers,who took part in the survey, experienced, initially, a feeling of disturbing strangeness when identifying a student with visual impairment in their class, however, contact with these students was important to reduce prejudices and to identify efficiencies in each student. . This work is based on the concept of Uncanny,, as elaborated by Freud in an article, "The uncanny”, published in 1919, in the discussions on psychoanalysis, teacher training and school inclusion conducted by professor and psychoanalyst Rinaldo Voltolini et al. (2018 ), in the Brazilian Constitution (1988) and in the status ( official document ) of the disabled person of July 2015. The Educational Product originated from this research, entitled “Life stories: Teachers, their paths and their experience with the visually impaired student”, will be published as an electronic book. This product aims to be used as a support material for teacher training and as a contribution to discussions about the school inclusion of people with visual impairments.